2014
DOI: 10.12659/msm.890459
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Urotensin II and its Receptor and the Clinicopathological Parameters of Breast Cancer

Abstract: BackgroundUrotensin II is a vasoactive polypeptide. It is known that some vasoactive polypeptides are produced and secreted by tumor cells, and act as a paracrine growth stimulant. The aim of this study was to examine the relationship between urotensin II and its receptor’s messenger RNA expression in breast cancer.Material/MethodsFifty-nine women with breast cancer were included in this study. The median age was 48 years. The relationships between urotensin II and urotensin II receptor mRNA expressions, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Furthermore, hUII was able to increase the proliferation rate of both tumour cell lines only observable after 48 h period incubation, at low and high hUII concentrations ( Figure 5C). These data are in a good agreement with studies showing that UT and/or UII are over-expressed in a wide variety of solid tumours [41][42][43][44]58] and participate in tumorigenic mechanisms such as cell migration and/or proliferation. These data have been reported for cancers of prostate [59], colon [44], liver [79] and lung [48] cancers.…”
Section: Ut Expression and Function In Dld-1 And A549 Tumour Cell Linessupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, hUII was able to increase the proliferation rate of both tumour cell lines only observable after 48 h period incubation, at low and high hUII concentrations ( Figure 5C). These data are in a good agreement with studies showing that UT and/or UII are over-expressed in a wide variety of solid tumours [41][42][43][44]58] and participate in tumorigenic mechanisms such as cell migration and/or proliferation. These data have been reported for cancers of prostate [59], colon [44], liver [79] and lung [48] cancers.…”
Section: Ut Expression and Function In Dld-1 And A549 Tumour Cell Linessupporting
confidence: 91%
“…The neuropeptide UII also participates in critical tumorigenic mechanisms, such as cell migration and/or proliferation [36,46,56] and tumour angiogenesis [57]. The urotensinergic receptor UT is present at the plasma membrane of tumoral cells from lung [42], breast [41], colon [58] or prostate cancer [59]. It has long been accepted that the internalisation of an agonist ligand-receptor complex justifies their use in diagnosing cancer, likely because of the accumulation of radioligand in the tumour cells [60,61].…”
Section: Synthesis and Radiolabelling Of Dota-huii And Dota-urantidementioning
confidence: 99%
See 1 more Smart Citation
“…As a powerful vasoactive peptide in mammals, initially UII/UTR is reported to play an important role in portal hypertension, renal disease and heart failure ( 5 ). Recent studies demonstrated that UII/UTR may involve in tumorigenesis and tumor progression in many malignant tumors ( 6 ), such as adrenal gland neoplasms ( 7 ), breast carcinoma ( 8 ), pulmonary adenocarcinoma ( 9 ), renal cell carcinoma and colon carcinoma ( 10 ). Our previous study demonstrated that UII and UTR are up-regulated in rat HCC model and human HCC tissue, exogenous UII can increase hepatic oval cell and HCC cell proliferation in vitro ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…(4) Insulin resistance: plasma levels of UII increase in diabetic patients (Totsune et al 2003) and high levels of UII can induce insulin resistance ) and inhibit glucose uptake in skeletal muscles ). (5) Carcinogenic effects: the expression of UII/UT is correlated with tumor progression, metastasis and prognosis (Wu et al 2010, Balakan et al 2014. UII mediates PKC-and ERK1/2dependent pro-mitogenic signaling pathways (Wang et al 2011) and induces cell transformation to malignant tumor phenotypes (Goldberg et al 2016).…”
Section: Introductionmentioning
confidence: 99%